2003
DOI: 10.1039/b210712k
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the cross-reactivity and binding sites characterisation of a propazine-imprinted polymer using the Langmuir-Freundlich isotherm

Abstract: In this paper, the Langmuir-Freundlich isotherm is used to model the interaction of several triazines (desethylatrazine, desisopropylatrazine, simazine, atrazine, propazine and prometryn) with a propazine-imprinted polymer and to explain the observed cross-reactivity. Different rebinding experiments (each herbicide alone or all together in a mixture) were carried out and the experimental binding isotherms were fitted to the Langmuir-Freundlich isotherm. The fitting coefficients obtained (total number of bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 16 publications
3
63
0
2
Order By: Relevance
“…There are more publications presented in the recent past that underline the utility of the crossreactivity potential of MIPs and we expect more reports on this theme to be published in the future [14][15][16][17].…”
Section: Crossreactivity Of Mipsmentioning
confidence: 92%
“…There are more publications presented in the recent past that underline the utility of the crossreactivity potential of MIPs and we expect more reports on this theme to be published in the future [14][15][16][17].…”
Section: Crossreactivity Of Mipsmentioning
confidence: 92%
“…In order to confirm the suitability of this strategy to prepare high quality molecularly imprinted polymers with homogenous binding site distribution, a new polymer using a different template (propazine) was prepared (MIP-P) and evaluated in the present work. Thus, the main aim of this paper is the characterisation and evaluation of the homogeneity of the binding sites of this polymer and to compare the results with those obtained for another non-covalent propazine-imprinted polymer prepared by bulk polymerisation (MIP-B) in a previous work [13]. This study was carried out by equilibrium rebinding experiments of not only propazine (template molecule) but also of other structurally related compounds able to interact with the obtained polymers.…”
Section: Introductionmentioning
confidence: 97%
“…It has been found that template membrane can be stored at room temperature in buffer solution for 12 weeks without showing any loss in sensitivity. The selectivity of the imprinted polymers seems to be governed by number and nature of interaction between substrate and polymer stationary phases, as well as by the shape of the print molecule and cavities in the polymers [16][17][18]. The nature of observed sensor responses might be explained by an assumption that interaction between the template molecule with the polymeric domain results in a conformational reorganization of the polymeric structure, affecting the diffusion of co-and counter ions.…”
Section: Discussionmentioning
confidence: 91%